RF Performance of USRP TwinRX Daughterboard Under Influence of Strong Interferers - Engelhardt, Maximilian; Andrich, Carsten; Ihlow, Alexander; Del Galdo, Giovanni (2022 16th European Conference on Antennas and Propagation, EuCAP 2022, 2022)
In this paper, we investigate the sensitivity of the software-defined radio (SDR) universal software radio peripheral (USRP) X310 with a TwinRX daughterboard to strong interferers. In a conducted test setup, the signal-to-interference-plus-noise ratio (SINR) is measured under the influence of a mock-up Long-Term Evolution (LTE) base station. The frequency of the interferer is varied to analyze the effects over a wide frequency band, whereby a distinction is made between signals inside and outside the intermediate frequency (IF) band. The former can cause clipping at the analog-to-digital converter (ADC), while the latter are to be suppressed in the analog part of the software-defined radio. Here, leakage and higher-order mixing products make the receiver sensitive to spurious frequencies, whereby the performance degradation is particularly noticeable near the first intermediate frequency (IF1) of 1.25 GHz. At this point, even an interference signal with-28 dBm peak envelope power (PEP) causes an SINR loss of 3 dB.
CRIS-Team Scopus Importer:2025-11-10
Keywords: out-of-band interferer; software-defined radio (SDR); TwinRX; USRP